Negara (Islam) Modern Vs Pemerintahan Islam; Studi Konsep Wael Al-Hallaq dalam Buku The Impossible State - Moad, Edward (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2015)
This paper deals with Wael Hallaq’s book, The Impossible State, published by Columbia University Press, 2013. By analysing of various Islamic political analysts, like Lama Abu Odeh, Andrew March, Carl Schmitt and John Gray, the author critiques it. Wael Hallaq has studied of the 'Islamic State', which was considered in the standard of a modern state, and he described as